Posibles determinantes del desempleo juvenil en Ecuador en el 2021 - Robles Castillo, Juan Carlos (2024)
Unemployment is a problem which has increased a long time ago raising social and economic consequences reflected most in exposed groups such us Young people. In spite of the exposed before the aim of the following research is to asses the relationship among posible variables that lead to youth unemployment in Ecuador by applying econometric techniques in order to reconmend policies to decrease youth unemployment. The recquiered data was taken from data base of the national survey of employment, unemployment and underemployment (ENEMDU) from 2021 published by the National Statistic and Census institute (INEC). To obtain the results there were used econometric models of nonlinear probabiliy in the maximun reliability. The results showt that youth people who live in urban areas tend most to be unemployed furthermore men tend most to be in this situation but also the ones who are not poor at all are unemployed in a high population. On the another side people who have a high degree have the biggest chance to be unemplyed. To summarize we suggest the government to set public policies such us encouraging youths by giving stimulus at the time of entrepreneuring in order to create their own profitable and reliable buissnes for present and future.